Особенности микроволновых переключателей на основе волноводного тройника - Горбенко, Е. А.; Бондаренко, И. Н. (ХНУРЕ, 2017)
The given work raises the number of questions, such as implementation of pulse shaping on the basis of resonator drives involves solving a number of problems related to the provision of fast switching microwave energy from a high-Q resonator drive to the load. Operation of the transmission lines for large values of the output signal amplitude. Adjustment of highly stable pump generator in the process of accumulation and radiation of the microwave energy and other.
Keywords: Микроволновые переключатели; Волноводный тройник